Maxillofacial trauma and its management presenting in tertiary care hospital in Lahore during Covid-19 pandemic - Syed Shumail Ahmad; Gulraiz Zulfiqar; Bisma Iftikhar (Journal of the Pakistan Medical Association, 2024)
Objective: The objective of this study was to assess the patterns of maxillofacial injuries, etiology and their management during the pandemic of Covid-19 in a tertiary care hospital in Lahore, Pakistan. Methods: This is a single center, prospective cross-sectional study. Patients from all age groups who were presented at the Emergency room of Jinnah Hospital Lahore and managed by the Oral and Maxillofacial Surgery Department during 1st December 2020 till 31st January 2021 were included. Data were analyzed using IBM SPSS for Windows, Version 20.0. Results: Total 202 patient were analyzed, 161 (79.7%) were male and 41 (20.3%) were females. Male to female ratio was 4:1. About fifty three percent of patients belonged to the age group 15-35 years. The most common cause was road traffic accidents (RTA), followed by fall. Eighty-three (41.1%) had only soft tissue injuries without any bony fracture and 119 (58.9%) had facial bones fractures. Zygomatic bone fracture was most common (53.8%) followed by mandible fracture (31.1%). Sixty-one out of 119 patients with fractures were treated with Open Reduction Internal Fixation (ORIF). Three patients had complete loss of vision because of facial trauma. Only 56 (28%) patients were managed under General Anesthesia. Conclusion: During initial pandemic era, a large majority of patients presented with maxillofacial injuries were young male adult. The most common cause of maxillofacial trauma was RTAs. Soft tissue injuries were predominant followed by facial bone fractures and zygomatic bone was more frequent among the fracture cases. Covid-19 pandemic increased the difficulties faced in the management of maxillofacial trauma patients. Keywords: Covid -19, Maxillofacial Injuries, Tertiary Care Centers.